Deprivation of Dietary Fiber Enhances Susceptibility of Piglets to Lung Immune Stress - Yang, Yi; Jiang, Xuemei; Cai, Xuelin; Zhang, Lijia; Li, Wentao; Che, Lianqiang; Fang, Zhengfeng; Feng, Bin; Lin, Yan; Xu, Shengyu; Li, Jian; Zhao, Xilun; et al. (Frontiers in Nutrition, 2022)
Growing evidence suggests that dietary fibre enhances short-chain fatty acid (SCFA) producing gut microbes, improving lung immunity against invading pathogens via the gut-lung axis. This study investigated the effects of dietary fibre on lung immune stress after challenge with complete Freund’s adjuvant (CFA) containing killed Mycobacterium tuberculosis. Thirty-six healthy hybrid Duroc, Landrace and Yorkshire male piglets (9.7 ± 1.07 kg, 35 ± 3 d) were randomly fed a low fibre (LF) diet formulated with semi-purified corn starch, soy protein concentrate and fishmeal or a high fibre (HF) diet composed of 1,000 g LF diet plus 20 g inulin and 100 g cellulose. Piglets were housed individually in the metabolism cages with eighteen ty replicates per group with one pig per cage. All piglets received similar levels of digestible energy and lysine and had similar weight gain.After dietary treatment for 28 d, nine piglets per group were intravenously administered CFA (0.4 mg/kg) or an equivalent amount of sterile saline in a 2 × 2 factorial arrangement. In piglets fed the LF diet, CFA caused lung damage and elevated serum C-reactive protein and relative mRNA expression of genes related to lung inflammation (NLRP3, Casp1, ASC, IL1β, IL18, Bax), Compared with the LF diet, the HF diet increased bacterial diversity and Deferribacteres (P = 0.01) in the phylum level and unidentified_Ruminococcaceae (P = 0.03) and Catenisphaera (P < 0.01) in the genus level. The HF diet improved increased SCFAs in faeces, blood, cecal and colonic digesta, reduced lung damage, and promoted lung recovery. Overall, dietary fibre deprivation enhanced the risk of piglets to lung immune stress, demonstrating the importance of dietary fibre in gut-lung health.